An Evaluation of Community-Based Interventions Used on the Prevention of Female Genital Mutilation inWest African Countries - Roselyn Ekundayo; Sally Robinson (European Scientific Journal, ESJ, 2019)
The traditional practice called Female Genital Mutilation has been recorded in several countries in Africa and in other regions around the world. Female Genital Mutilation is regarded as a major Public Health burden due to the extensive health risks associated with the procedure and community-based interventions has been prescribed to eliminate the practice. This paper presents a review of published literature about community-based interventions carried out to prevent Female Genital Mutilation in West Africa between the years 2000-2013. A literature search was conducted for papers published between the years 2000 - 2013. Papers were reviewed if they reported a positive change in knowledge, attitude and behaviour towards FGM. Twenty papers met the inclusion criteria. A total of eight types of methods were identified: Advocacy Campaigns, Health Education, Sensitization Workshops, Community dialogue, Media campaigns (radio, newspaper, film shows, information posters) counselling, role plays and Skills training. This study identified that these interventions utilised health promotion models such as the behaviour change, client-centred/empowerment, social change and most commonly the educationalmodel. None of the interventions were based on the medicalmodel of health promotion. Hence, it seems an incorporation of the medical and educational models of health promotion could result in a greater impact in community-based interventions to prevent FGM.